EXPLORING ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) AND FINANCIAL INFLUENCES ON STOCK RETURNS: EVIDENCE FROM ASEAN - Mulyadi, Heldy; Musviyanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study investigates the effects of ESG scores, profitability, and dividend policy on the stock returns of companies listed in ASEAN capital markets from 2020 to 2023. Using a quantitative approach, the research employs secondary data from MSCI ESG scores, company websites, and stock exchanges, analyzed through multiple regression with SPSS 27.0. The results indicate that profitability has a significantly positive effect on stock returns, dividend policy has a significantly negative effect, while the ESG score shows no significant effect. These findings suggest that ASEAN investors still prioritize short-term financial indicators, viewing profitability as a positive signal and dividend distribution as a negative one, while ESG factors remain underemphasized in investment decisions. The study contributes to signaling theory by providing evidence from ASEAN markets and offers implications for managers and policymakers seeking to strengthen the role of sustainability information in investment practices.